Understanding climate change and rural livelihoods in Zimbabwe: adaptation by communal farmers in Ngundu, Chivi District - Nciizah, Elinah (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
Climate change and variability is a global phenomenon which has deeply localised patterns, dynamics and effects. Amongst those people who are particularly vulnerable to climate change effects are small-scale farmers who are dependent in large part on rain-fed agriculture in pursuing their livelihoods. This is true of small-scale farmers in contemporary Zimbabwe and, more specifically, farmers in communal areas. At the same time, at international and national levels, there are attempts currently to minimise the effects of, and to adapt to, climate change. However, adaptation measures also exist at local levels amongst small-scale farmers, such as communal farmers in Zimbabwe. In this context, as its main objective, this thesis examines climate change and small-scale farmer livelihood adaptation to climate change with specific reference to communal farmers in Chivi District in Zimbabwe and, in particular, in Ward 25 which is popularly known as Ngundu. In pursuing this main objective, a number of subsidiary objectives are addressed, including a focus on the established livelihoods of Ngundu farmers, the perceptions and concerns of Ngundu farmers about climate change, the coping and adaptation measures of Ngundu farmers, and the enablements and constraints which affect attempts by Ngundu farmers to adopt such measures. The fieldwork for the thesis involved a diverse array of research methods, such as a questionnaire survey, life-history interviews, key informant interviews, focus group discussions and transect walks. In terms of theoretical framing, the thesis makes use of both middle-level theory (the Sustainable Livelihoods Framework) and macro-theory in the form of the sociological work of Margaret Archer. Combined, these two theories allow for a focus on both structure and agency when seeking to understand livelihood adaptations to climate change by communal farmers in Ngundu. The thesis concludes that there are massive constraints inhibiting adaptation measures by Ngundu farmers, but that this should not distract from the deep, often historically-embedded, concerns of Ngundu farmers about climate change and the multiple ways in which they express agency in and through adaptation and coping activities. It also highlights the need for more specifically sociological investigations of climate change and small-scale farmer adaptation, as well as the need for localised studies which are able to identify and analyse the specificities of adaptation.
Keywords: Agriculture -- Zimbabwe; Agriculture -- Climatic factors -- Chivi District (Zimbabwe); Chivi District (Zimbabwe) -- Rural conditions